The investigation of heat stress among workers in pineapple plantation - Mohamad Ikhwan, Mohd Rashid (2018)
Working in the pineapple plantation is quite challenging due to working under hot sun with long period without any mechanical ventilation or other technical methods. Physical work in hot and humid environments imposes health risks, productivity falling and safety problems on workers. A cross-sectional study had been conducted at pineapple plantation in Temerloh, Pahang. The main objective of this to identify the level of heat exposure among the pineapple plantation workers and its effect with physiological parameters such as body core temperature, blood pressure and heart rate of workers at pineapple plantation. Environment parameter such as WBGT(in) and WBGT (out) was measured. The questionnaire was used to determine respondent's socio-demographic data and heat stress symptoms. This study found that WBGT index value exceeded the limit of ACGIH. The Pearson correlation test showed that there is week correlation between WBGT index with body core temperature, blood pressure and heart rate. This finding suggested to the management to follow heat stress management guidelines, implement work based on 50% work and 50% rest because the workers are exposed to the risk of heat stress.